2020
DOI: 10.1016/j.xphs.2019.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Native Reversible Self-Association of a Monoclonal Antibody Mediated by Fab-Fab Interaction

Abstract: The native reversible self-association of monoclonal antibodies has been associated with high viscosity, liquid-liquid, and liquid-solid phase separation. We investigated the native reversible self-association of an IgG1, which exerts this association even at low protein concentrations, in detail to gain further understanding of this phenomenon by extensive characterization of the association as a function of multiple factors, namely pH, temperature, salt concentration, and protein concentration. The nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Taken together, these findings indicate that protonation states are not the primary source of error in our hydrophobicity calculations. On the other hand, the abovementioned study by Gentiluomo et al (8) found a strong influence of the pH on aggregation. However, we note that hydrophobicity and aggregation propensity are different properties.…”
Section: Effects Of Protonation State Sampling On Hydrophobicitymentioning
confidence: 81%
See 2 more Smart Citations
“…Taken together, these findings indicate that protonation states are not the primary source of error in our hydrophobicity calculations. On the other hand, the abovementioned study by Gentiluomo et al (8) found a strong influence of the pH on aggregation. However, we note that hydrophobicity and aggregation propensity are different properties.…”
Section: Effects Of Protonation State Sampling On Hydrophobicitymentioning
confidence: 81%
“…A major problem in the development process is the inherent tendency of some concentrated protein solutions to form aggregates. This problem may be influenced by various factors such as temperature, mechanical stress, and pH ( 7 , 8 , 9 ). Aggregation can be reversible or irreversible and covalent or noncovalent, and the resulting aggregates may be soluble or insoluble ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of the interface sites can be driven by both amino acid sequence and higher order structure of the therapeutic. There are examples of dimer formation being driven by Fab-Fab, Fc-Fc and Fab-Fc interactions (15)(16)(17)(18)(19). However, the behavior of dimers with regards to driving aggregation of mAbs is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…, and liquid-liquid phase separation 5,6 . At the root of these phenomena are complex protein-protein interactions (PPI) that are governed by the intrinsic molecular properties of the protein molecules themselves 7 , as well as the extrinsic solution and environmental conditions like pH, temperature, protein concentration and the presence of excipients. While there are many different instruments available to the pharmaceutical scientist for measuring opalescence, the specific capabilities, optical configurations and calibration practices can vary considerably and are not always evident to the end user.…”
Section: Introductionmentioning
confidence: 99%